Advancing digital sensing in mental health research - Samir Akre; Darsol Seok; Christopher Douglas; Adrian Aguilera; Simona Carini; Jessilyn Dunn; Matthew Hotopf; David C. Mohr; Alex A. T. Bui; Nelson B. Freimer (npj Digital Medicine)
Abstract Digital sensing tools, like smartphones and wearables, offer transformative potential for mental health research by enabling scalable, longitudinal data collection. Realizing this promise requires overcoming significant challenges including limited data standards, underpowered studies, and a disconnect between research aims and community needs. This report, based on the 2023 Workshop on Advancing Digital Sensing Tools for Mental Health, articulates strategies to address these challenges to ensure rigorous, equitable, and impactful research.